Historians' approach to the history of the kurds: ibn khaldun as an analytical and critical study - Abdul Fattah Zahra, Abdul Ghani (Humanities Journal of University of Zakho, 2023)
Ibn Khaldun cared about the Kurds in his well-known lessons of history, Diwan al-Mubtada wa al-Khabar in the important history of the Arabs and Berbers and their contemporaries, as well as in his introduction known as The Introduction of Ibn Khaldun. So, he began by mentioning their geographical location, their lands and their mountains, then he moved to their history from the era of the inception of Islam until its era. He also mentioned their participation in political events: their small roles when they are part of an army, or their roles in a division in a leader’s campaign, such as the Kurdish division in the army of Nur al-Din Mahmud headed by Asad al-Din Shirkuh, or their attempt to establish an emirate or a state, such as the attempt of the Hamidian Kurds led by Abu al-Hussein known as Bad in the establishment of a state in Mosul in the year three hundred and sixty-seven AH. Besides, he mentioned some Kurdish emirates from their inception to end, such as the emirate of Bani Marwan in Diyarbakir, and the state of Bani Ayyub in Egypt and the Levant. Furthermore, he followed the Kurdish prominent personalities who migrated to different countries, such as Khorasan, India, Iraq, Egypt, the Levant and the countries of the Maghreb. Ibn Khaldun agreed with the historians in most of his novels, and disagreed with them in some others. Ibn Khaldun did not neglect to mention some of the cultural aspects of the Kurds, such as their interest in science and poetry, and the economic and social conditions of their country. This study chose Ibn Khaldun as a model because he belongs to the countries of the Maghreb. So it will investigate the extent of Moroccans' interest in the history of the countries and sects of the East, including the Kurds, and the extent of their interest in seeking honesty in mentioning their history.